Fabrication of highly sensitive flexible phototransistors through a unidirectional floating film transfer method using P4T2F-HD thin films - Shyam R.; Manaka T.; Prakash R. (My University, 2025)
This study introduces a fabrication technique for fabricating highly sensitive, flexible organic phototransistors (OPTs) suitable for advanced wearable and smart home applications. Conventional methods of fabricating OPTs typically encounter significant challenges due to solvent-induced degradation of polymer gate dielectrics, adversely affecting the device performance. To overcome these issues, we employed a Unidirectional Floating Film Transfer Method (UFTM) for depositing P4T2F-HD thin films. This technique is designed to minimize the impact on the underlying organic dielectric layers, thus maintaining their structural integrity and orientation. Using the UFTM, we successfully formed highly oriented semiconductor films. The phototransistors produced through this method showed remarkable performance enhancements, achieving a sensitivity of 167%, a high responsivity of 292 A W−1, and a detectivity of 8.5 × 1013 Jones under a light intensity of 125 μW cm−2. Additionally, these devices demonstrated exceptional durability, maintaining robust performance over time and withstanding repeated mechanical stress in both parallel and perpendicular bending orientations relative to the channel. This research underscores the potential of the UFTM in advancing the functionality and durability of OPTs for practical applications in flexible electronics. © 2024 The Royal Society of Chemistry.